2023
DOI: 10.3390/land12040824
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Industrial Agglomeration on Urban Land Green Use Efficiency and Its Spatio-Temporal Pattern: Evidence from 283 Cities in China

Abstract: Industrial agglomeration is one of the primary driving factors in city creation, and the improvement of urban land green use efficiency (ULGUE) is an important part in green development. This study concentrates on the impact of industrial agglomeration on ULGUE in the process of urbanization. Based on the panel data of 283 cities in China from 2003 to 2019, this paper constructs a super efficiency SBM-DEA model including unexpected outputs to evaluate ULGUE. Using a spatial Durbin model, we examine the spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Although the ECRT is not combined with LGUE, the literature presents a near consensus that market-oriented ER improves LGUE. Xu et al (2021) [14] found that a certain degree of ER can increase the environmental pressure on enterprises, thereby improving the LGUE of cities. Bian and Zhong (2023) [41] found that market-oriented ER can optimize multi-dimensional output per unit of land through market-oriented means and reduce pollution emissions, thereby improving the LGUE.…”
Section: Did Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ECRT is not combined with LGUE, the literature presents a near consensus that market-oriented ER improves LGUE. Xu et al (2021) [14] found that a certain degree of ER can increase the environmental pressure on enterprises, thereby improving the LGUE of cities. Bian and Zhong (2023) [41] found that market-oriented ER can optimize multi-dimensional output per unit of land through market-oriented means and reduce pollution emissions, thereby improving the LGUE.…”
Section: Did Resultsmentioning
confidence: 99%
“…Scholars have used an improved unexpected output super efficiency SBM model to measure LGUE comprehensively, analyzed the current situation and characteristics of urban LGUE in China [10], and pointed out that economic development [11] and the degree of openness to the outside world [12] can affect urban LGUE. The important role of local government behavior in improving the LGUE has also been studied [13,14]. Hence, can the ECRT pilot promote the improvement of urban LGUE?…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al (2022) indicate that the degree of marketization of land elements significantly contributes to the improvement of construction land and promotes the overall efficiency of ULGUE. GOV: Denoted by the utilization rate of industrial solid waste. The disposal of industrial waste reflects the government's awareness of environmental protection and the implementation of environmental protection policies, which profoundly impact the transformation of polluting enterprises and efficiency gain (Xu et al, 2021). …”
Section: Methodsmentioning
confidence: 99%
“…GOV: Denoted by the utilization rate of industrial solid waste. The disposal of industrial waste reflects the government's awareness of environmental protection and the implementation of environmental protection policies, which profoundly impact the transformation of polluting enterprises and efficiency gain (Xu et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…As green development and related theoretical analysis have gradually matured, studies on ULGUE have gradually shifted toward empirical research measuring ULGUE and analyzing its spatiotemporal characteristics and driving factors, according to the concept of sustainable land use. In terms of choosing the measurement and empirical research methods for analyzing the spatial of ULGUE, existing studies have generally adopted classical models such as DEA, the spatial Durbin model, and the STIRPAT model [8,9]. In addition to this, the non-radial directional distance function approach has been used to measure the green utilization efficiency of agricultural land [10].…”
Section: Introductionmentioning
confidence: 99%